HIV AND LYMPHOMA: FROM EPIDEMIOLOGY TO CLINICAL MANAGEMENT - Alessandro Re; Chiara Cattaneo; Giuseppe Rossi (Mediterranean Journal of Hematology and Infectious Diseases)
Patients infected with human immunodeficiency virus are at increased risk for developing both non Hodgkin’s lymphoma (NHL) and Hodgkin’s lymphoma (HL). Even if this risk has decreased for NHL after the introduction of combination antiretroviral therapy (cART), they remain the most common AIDS-related cancer in the developed world. They are almost always of B-cell origin, and some specific lymphoma types are more common than others. Some of these lymphoma types can occur in both HIV-uninfected and infected patients, while others preferentially develop in the context of AIDS. HIV-associated lymphoma differ from lymphoma in the HIV negative population in that they more often present with advanced disease, systemic symptoms, and extranodal involvement and are frequently associated with oncogenic viruses (EBV and/or HHV-8). Before the introduction of cART, most of these patients could not tolerate the treatment strategies routinely employed in the HIV-negative population. The widespread use of cART has allowed for the delivery of full-dose and dose-intensive chemotherapy regimens with improved outcomes that nowadays can be compared to those seen in non-HIV infected patients. However, a great deal of attention should be paid to opportunistic infections and other infectious complications, cART-chemotherapy interactions, and potential cumulative toxicity. In the context of relatively sparse prospective and randomized trials, the optimal treatment of AIDS-related lymphomas remains a challenge, particularly in patients with severe immunosuppression. This paper will address epidemiology, pathogenesis, and therapeutic strategies in HIV-associated NHL and HL.